Possible factors influencing high serum Prostate-specific Antigen (PSA) in Indonesian patients with Benign Prostatic Hyperplasia (BPH) (Medical Journal of Indonesia, 2001)
Benign prostatic hyperplasia (BPH) cases in Indonesia frequently associated with high serum prostate specific antigen (PSA). To explore possible factors that could increase serum PSA level, we performed a retrospective, cross-sectional study on 805 consecutive patients in Sumber Waras and Dr. Cipto Mangunkusumo Hospitals from 1994 to 1997. Clinical manifestations were evaluated and prostate biopsies were performed if indicated. Complete histopathological data were only available in 82 BPH patients with no urinary retention from 1998-1999 and a thin section of paraffin blocks of BPH patients which still could be found from 1994-1999 was analyzed using flow cytometer to obtain the S-phase fraction as a parameter of proliferative activity, From 805 patients, 461 (57%) presented with urinary retention and need to be catheteized. Catheteization significantly increased PSA level if compared to noncatheterized patients (16.3 vs. 6,8 ng/mL, p= 0,000). Another data of 82 uncatheteized patients from 1998-1999 has revealed that 79 patients (96.3%) had chronic prostatitis and 19 (23.2%) showed the presence of prostatic-intraepithelial neoplasia (PIN) with an increase of PSA level (5.4 ng/mL). The S-phase fraction of BPH without PIN cases was significantly higher in cases with PSA > 4 ng/ml than patients with PSA < 4 ng/ml (I3.1% vs. 8.9%, p=0,008). As conclusion, the high serum PSA level was mostly due to urethral catheteization and increased prostate volume. There was a tendency of increasing PSA in subclinical inflammation and PIN. Cases with high PSA also showed high proliferative activities which is suggestive of mitogenic activity. (Med J Indones 2001; 10:22-8) Keywords: BPH, high PSA, PIN, proliferative activity, s-phase fraction